Deciphering and prediction of plant dynamics under field conditions. (April 2015) - Izawa, Takeshi
Highlights: Field transcriptome data can be modeled with fluctuating environmental factors. Threshold and perception time are key factors of plant responses to the environment. Gating effect to plant responses is a considerable choice during model selection. Coherent methods of gene selection for traits from transcriptome data are required. Phenology models will be improved with knowledge of molecular genetics. Abstract : Elucidation of plant dynamics under fluctuating natural environments is a challenging goal in plant physiology. Recently, using a computer statistics integrating a series of transcriptome data of field-grown rice leaves during an entire crop season and several corresponding environmental data such as solar radiation and ambient temperature, most parts of transcriptome have been modeled. This reveals the detailed contributions of developmental timing, circadian clocks and each environmental factor to transcriptome dynamics in the field and can predict transcriptome dynamics under given environments. Furthermore, some traits such as flowering time in natural environments have been shown to be predicted by mathematical models based on gene-networks parameterized with data obtained in the laboratory, and phenology models refined by knowledge of molecular genetics. New molecular physiology is beginning in plant science.